Prevalence of Potential Drug-Drug Interactions in Neonatal Intensive Care Unit of a Tertiary Care Hospital: A Prospective Observational Study: Pharmaceutical Science-Pharmacy practice for Good Health - Sara Nasrollahi; Neelathahalli Kasturirangan Meera (International Journal of Life Science and Pharma Research, 2022)
Hospitalized neonates in neonatal intensive care unit (NICU) are usually exposed to great number of drugs and they are susceptible to adverse outcomes due to their immature functioning organs and reasons like inappropriate dosing or choice of medicines. We aimed to assess the prevalence and characteristics of potential drug- drug interactions (pDDIs) in the NICU. In this prospective observational study, case sheets of neonates who were in the NICU for more than 24 hours and were administered with at least two drugs were analysed for pDDIs by using Lexicomp database. All pDDIs were classified according to their severity, reliability, risk level and their underlying mechanisms. Potential predictors and potential outcomes of pDDIs were also evaluated. We found that 66.2% of neonates were exposed to at least one pDDI. Total of 902 pDDIs comprising of 70 distinct pDDIs were identified of which 88% were moderate in severity. 11.8% and 0.2% of them were major and minor respectively. Most of pDDIs belonged to category C (61.4%) and category D (30%) of risk level. Majority of interactions had pharmacodynamic mechanism (65.7%) and fair scientific evidences (68.6%). The most common potential adverse drug events included increased sympathomimetic effects, nephrotoxicity and alteration of serum concentration of drugs. Systemic anti-infective were involved in majority of interactions. pDDIs were more prevalent in neonates with gestational age of <32 weeks, >11 days of hospital stay and those who received >11 concomitant drugs. Identification of pDDIs and monitoring the neonates for potential adverse outcomes is mandatory especially in high risk conditions to avoid or minimize the actual harm.